A New Method to Estimate Risk and Return of Nontraded Assets from Cash Flows: The Case of Private Equity Funds - Driessen, Joost; Lin, Tse-Chun; Phalippou, Ludovic (Journal of Financial and Quantitative Analysis, 2012)
Abstract We develop a new methodology to estimate abnormal performance and risk exposure of nontraded assets from cash flows. Our methodology extends the standard internal rate of return approach to a dynamic setting. The small-sample properties are validated using a simulation study. We apply the method to a sample of 958 private equity funds. For venture capital funds, we find a high market beta and underperformance before and after fees. For buyout funds, we find a relatively low market beta and no evidence for outperformance. We find that self-reported net asset values significantly overstate fund values for mature and inactive funds.